Antiviral effects of mogroside V against porcine reproductive and respiratory syndrome virus in vitro - Liang, Longhua; Huang, Xiaohui; Qin, Guoxi; Ma, Xiaoyu; He, Rijing; Dai, Hongpeng; Zhang, Zhen; Yang, Xiaogan; Liang, Xingwei (Frontiers in Microbiology, 2025)
Porcine reproductive and respiratory syndrome virus (PRRSV) infection has inflicted devastating impacts on the global swine industry, while current vaccines provide limited protection against this disease. Mogroside V (MV), a triterpenoid compound derived from Siraitia grosvenorii, exhibits diverse biological activities including antioxidant, anti-inflammatory, and anti-cancer properties, with the capacity to scavenge free radicals and mitigate oxidative stress. In this study, MV was administered to PRRSV-infected cells via three distinct treatment modalities. Our findings demonstrate that MV effectively blocks or suppresses infections caused by diverse PRRSV subtypes in porcine alveolar macrophages (PAMs) and Marc-145 cells. MV exhibited significant dose-dependent antiviral efficacy, with viral titers and mRNA expression inhibited by over 90% at a concentration of 400 μM. Comparative analysis further revealed substantial variations in antiviral efficacy among the different treatment protocols. Notably, PRRSV employs immune evasion mechanisms to suppress host innate immunity. MV not only directly inhibited PRRSV replication but also significantly upregulated the gene expression of immunomodulatory cytokines (IL-1, IL-2, IL-8, IL-18; P < 0.05), suggesting a dual mechanism of antiviral action. These findings underscore the antiviral bioactivity of MV and highlight its potential as a novel therapeutic candidate for PRRSV intervention.